Recalibrate: changing paradigms - Singh, N. K.; Mishra, P. K. (New Delhi Rupa, 2022)
The world today is in constant flux. However, rarely has the pace of change been so multidimensional; faster than our ability to adjust. Geopolitics is changing; the land wars in Europe are evolving; technology is offering newer possibilities every day; climate change is making long-term survival look difficult; and the biology of the pandemic continues to surprise us. None of this may be new, but their constellation is perhaps unique.
Keywords: ECONOMIC POLICY: GOVERNMENT POLICY; Planning commission; Fiscal federalism -- Policies